Knowledge and Skills of Community Health Workers in Filling of Towards Health Card (Kartu Menuju Sehat) - Adhyanti, Adhyanti; Nurjaya, Nurjaya; Rezkiana, Fidya (Media Publikasi Cendekia Indonesia, 2023)
The knowledge and skills of community health workers (Posyandu’s cadre) in filling of Towards Health Card (KMS) play an important role in monitoring the growth of toddlers. To analyze the knowledge and skills of community health workers in filling out the health card (KMS) in the Kayuwou Health Center Work Area, Donggala Regency, Central Sulawesi. This study was an analytic observational study using a cross-sectional design with a total sample of 39 people taken by simple random sampling. Data collection techniques were carried out by interviews and performance. Analysis was performed by chi-square test. The results showed that most of the respondents had sufficient knowledge about KMS (59.0%) and were classified as skilled in completing KMS (61.5%). The working status of cadres has a significant relationship with the skills of cadres in completing the KMS (p<0.05). It is better if people who are appointed as community health workers are people who are not working so they can focus more on carrying out their duties as cadres.